Effect of non-genetic factors on semen characteristics of Murrah Bull under Tropical Condition - Meena, Sunil Kumar Meena; Prakash Chand Sharma; Samita Saini; Priyanka Swami; Nirmal Jeph; Navav Singh; Mahendra Kumar Meena (Indian Journal of Dairy Science, 2023)
The objective of this study was to assess the effect of non-genetic factors on semen characteristics of 22479 ejaculates from 139 Murrah bulls during the period of 2017-2020 was analyzed under tropical conditions, maintained and recorded at Frozen Semen Bank (FSB), Bassi, Rajasthan Cooperative Dairy Federation, (India) as well as in Information Network for Animal Productivity & Health (INAPH) application maintained at National Dairy Development Board (NDDB). Results were recorded as 2.94±0.03 mL for volume, 1234.72±13.51million/mL for sperm concentration and 68.44±0.25 percentage for motility. Statistical analysis presented a significant difference for all semen parameters with studied non-genetic factors except semen collector for motility traits. Also, seasonal dynamics presented winter as the most suitable season for semen collection under tropical conditions. Age of bull showed significantly increased values for all semen traits with the increasing age of bull except motility traits. Data analysis in this regard may be utilized to enhance the fertility rate by increasing the semen quality.